2016
DOI: 10.1007/s00213-016-4299-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine withdrawal alters neural responses to psychosocial stress

Abstract: Psychosocial stress is considered to be an important mechanism underlying smoking behavior and relapse. Thus, understanding the effects of acute nicotine withdrawal on responses to stress is important to intervene to prevent stress-induced relapse. The current study investigated the neural correlates of psychosocial stress during acute nicotine withdrawal in chronic smokers. Thirty nine treatment-seeking smokers were randomized to one of two conditions (abstinent 24 hours (n=21) or smoking as usual (n=18)). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 61 publications
2
14
0
3
Order By: Relevance
“…In one study of satiated smokers, stress produced deactivation in limbic (e.g., amygdala, hippocampus, striatum) and prefrontal regions (e.g., ventromedial PFC, anterior cingulate cortex) that predicted increases in subsequent cue-induced craving responses (Dagher, Tannenbaum, Hayashi, Pruessner, & McBride, 2009). On the other hand, Ashare and colleagues (Ashare et al, 2016) reported increased neural stress reactivity in four brain regions, including anterior cingulate, precuneus, and inferior frontal gyrus; further, deprived smokers exhibited significantly greater activation compared to those who were non-deprived. The latter findings are consistent with prior reports in other drug using groups showing stress-induced increases (rather than decreases) in neural activity (e.g., Potenza et al, 2012; Sinha et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…In one study of satiated smokers, stress produced deactivation in limbic (e.g., amygdala, hippocampus, striatum) and prefrontal regions (e.g., ventromedial PFC, anterior cingulate cortex) that predicted increases in subsequent cue-induced craving responses (Dagher, Tannenbaum, Hayashi, Pruessner, & McBride, 2009). On the other hand, Ashare and colleagues (Ashare et al, 2016) reported increased neural stress reactivity in four brain regions, including anterior cingulate, precuneus, and inferior frontal gyrus; further, deprived smokers exhibited significantly greater activation compared to those who were non-deprived. The latter findings are consistent with prior reports in other drug using groups showing stress-induced increases (rather than decreases) in neural activity (e.g., Potenza et al, 2012; Sinha et al, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…This paper reports on the effects of abstinence versus satiety on neural cue reactivity as part of a larger ongoing study of neural predictors of smoking relapse. Sample size for the present report was based on an estimated effect size of abstinence on domains involved in smoking behavior (eg, cue reactivity, stress reactivity); a sample of n = 75 provides 80% power to detect an effect size of Cohen's d = 0.33, similar to effect sizes observed in previous studies . Participants were 75 treatment‐seeking smokers ages 18 to 65 who reported smoking ≥5 cigarettes/day for ≥6 months and were recruited through media advertisements.…”
Section: Methodsmentioning
confidence: 99%
“…Neural measures of stress response, such as functional magnetic resonance imaging (fMRI), provide an objective method to interrogate abstinence-induced changes in stress reactivity and may provide insight beyond what can be obtained with cortisol or subjective measures. [18][19][20] Two commonly used paradigms for stress induction in the scanner include individually calibrated scripted stress tasks, 21 and the Montreal Imaging Stress Task (MIST), a psychosocial stress task that requires subjects to perform challenging mental arithmetic in the presence of negative social evaluation. 22,23 Individualized stress scripts consistently increase activity in executive control and limbic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Abstinence from smoking (vs. satiety) was associated with stressrelated increases in activation in the inferior frontal gyrus (IFG), anterior cingulate cortex, precuneus, and supramarginal gyrus. 18 Neither of these studies tested whether brain response and subjective stress response were associated.…”
Section: Introductionmentioning
confidence: 99%